Observing the corporate and Shari’ah governance profiles of Islamic banks in Malaysia: do they matter? / Memiyanty Abdul Rahim, Abdul Rahim Abdul Rahman and Syed Musa Alhabsi - Abdul Rahim, Memiyanty; AAbdul Rahman, bdul Rahim; Alhabsi, Syed Musa (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Corporate and Shari’ah governance are vital for enhancing accountability of the key players and corporate performance. This paper aims to observe corporate (CG) and Shari’ah governance (SG) profiles of the Islamic banks in Malaysia since the effective implementation of Shari’ah governance framework from 2011 till present. The relevant information for CG and SG were retrieved from Annual Report of 13 Islamic Banks. CG profile was represented by board size, independent non-executive director, board competency, and board meeting. Shari’ah board and Shari’ah board meeting were the profiles for the SG. The CG and SG profiles were only being chosen from the board and Shari’ah board perspective. They are the key player in making decisions and steering the business operation, process and activities. The observations have been done using trend analysis (graph) and descriptive statistical results. The findings showed that majority of Islamic banks have fulfilled the corporate and Shari’ah governance requirements. This would perhaps give positive indicators to enhance economic growth and stability for Malaysia. The CG and SG profiles can be used further in any empirical testing to examine their influence on performance or any other measurements.